Sensing and monitoring technologies for mines and hazardous areas : monitoring and prediciton technologies - Chaulya, S. K.; Prasad, G. M. (Amsterdam, Netherlands : Elsevier, 2016)
"This authoritative reference presents the fundamentals of mining related geotechnical risk and the latest advances in sensing and data communication for preventing accidents and providing early warnings. Opencast mining operations involve huge quantities of overburden removal, dumping, and backfilling in excavated areas. Substantial increases in the rate of accumulation of waste dumps in recent years has resulted in greater height of dumps and also has given rise to the danger of dump failures as steeper open pit slopes are prone to failure. These failures lead to loss of valuable human lives and damage to mining machinery. This book presents the most recent advances in gas sensors, methane detectors, and power cut-off systems. It also introduces monitoring of the gas strata and environment, and an overview of the use of Internet of Things and cloud computing for mining sensing and surveillance purposes.... This volume covers the latest findings and technology to prevent mining accidents and mitigate the inherent risk of the activity."--
Slope Failure Mechanism and Monitoring Techniques -- Mine Transport Surveillance and Production Management System -- Gas Sensors for Underground Mines and Hazardous Areas -- Local Methane Detection and Power Cut-Off System -- Integrated Mine Environment and Strata Condition Monitoring System -- Formation of Digital Mine Using the Internet of Things -- Application of Cloud Computing Technology in Mining Industry.
Includes index.
Print version record.
Includes bibliographical references at the end of each chapters and index.
Keywords: Mines and mineral resources -- Remote sensing; TECHNOLOGY & ENGINEERING -- Mining; Mines and mineral resources -- Remote sensing; Mines et extraction; Electronic books; Electronic book